2013
DOI: 10.1080/19338244.2013.828674
|View full text |Cite
|
Sign up to set email alerts
|

Aspartame and Risk of Cancer: A Meta-analytic Review

Abstract: Aspartame (APM) is the most commonly used artificial sweetener and flavor enhancer in the world. There is a rise in concern that APM is carcinogenic due to a variation in the findings of the previous APM carcinogenic bioassays. This article conducts a meta-analytic review of all previous APM carcinogenic bioassays on rodents that were conducted before 31 December 2012. The search yielded 10 original APM carcinogenic bioassays on rodents. The aggregate effect sizes suggest that APM consumption has no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“… has been heavily criticised, and it has been argued that the proposed link between aspartame consumption and brain malignancies is subject to the ecological fallacy . Most recently, a systematic review and meta‐analysis of 10 aspartame carcinogenic bioassays in rodents found that aspartame consumption has no significant carcinogenic effect .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… has been heavily criticised, and it has been argued that the proposed link between aspartame consumption and brain malignancies is subject to the ecological fallacy . Most recently, a systematic review and meta‐analysis of 10 aspartame carcinogenic bioassays in rodents found that aspartame consumption has no significant carcinogenic effect .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in humans that originally demonstrated this association have since been heavily criticised , and animal data also cast doubt on the link between aspartame and cancer. An extensive meta‐analysis of aspartame carcinogenic bioassays in rodents conducted in 2013 concluded that aspartame consumption had no significant impact on cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…91 A meta-analysis of studies of aspartame in rats showed no association between aspartame and cancer. 92 A review of human (adult) cohort and case control studies showed no relationship between most types of cancer and aspartame use. 18,51,92,93 Newer data have failed to demonstrate an association between NNS use and cancer.…”
Section: Nns Use and Cancer Riskmentioning
confidence: 99%
“…92 A review of human (adult) cohort and case control studies showed no relationship between most types of cancer and aspartame use. 18,51,92,93 Newer data have failed to demonstrate an association between NNS use and cancer. 90 The long latency period, the penetrance of NNSs into the food supply (making it difficult to isolate an adequate unexposed control group), and the diversity of potential mechanisms have made it difficult to definitively exclude potential carcinogenic properties of NNSs but also make it difficult to conclude that there is any such association.…”
Section: Nns Use and Cancer Riskmentioning
confidence: 99%
“…Az aszpartámot számos betegségcsoport -daganatok, szív-és érrendszeri betegségek, idegrendszeri és viselkedésbeli zavarok, immuneltérések, látáskárosodás, emésztési, urológiai, nőgyógyászati problémák -kialakulásának okozójaként emlegetik [55,56].…”
Section: Aszpartám (E951)unclassified